1977
DOI: 10.1677/joe.0.0730091
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Receptor Levels and Hormone, Rna and Protein Metabolism in the Genital Tract During the Oestrous Cycle of the Ewe

Abstract: The concentrations of soluble oestradiol and progesterone receptor proteins and several metabolic activities were measured in the genital tracts of ewes killed on Days 0 (oestrus), 2, 5, 10 or 14 of the oestrous cycle. In caruncular endometrium and in whole uterus the concentrations of oestradiol receptor (pmol steroid bound/mg tissue DNA) were highest at oestrus and declined steadily thereafter to minimal values at Day 14. The concentrations of progesterone receptor were highest on Days 0-5, then declined to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 19 publications
7
29
0
Order By: Relevance
“…The initial effect of estradiol on receptor levels was inhibitory, but the subsequent response was to increase receptor expression. The initial suppression on the binding capacity of ER and PR is different from the reported receptor up-regulation induced by estrogen in cyclic and ovariectomized ewes [25,31,32]. It has been suggested that E2 regulation of uterine ER in rat is dose dependent, as demonstrated by the positive and negative effects of low and high doses of E2 on ER concentrations, respectively [20].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The initial effect of estradiol on receptor levels was inhibitory, but the subsequent response was to increase receptor expression. The initial suppression on the binding capacity of ER and PR is different from the reported receptor up-regulation induced by estrogen in cyclic and ovariectomized ewes [25,31,32]. It has been suggested that E2 regulation of uterine ER in rat is dose dependent, as demonstrated by the positive and negative effects of low and high doses of E2 on ER concentrations, respectively [20].…”
Section: Discussionmentioning
confidence: 89%
“…An example of this action is the regulation of the expression of their own receptor; the E-receptor complex stimulates both ER and PR gene expression in uteri of several mammalian species, while the P-receptor complex reduces levels of both receptors [4]. This is displayed by the variations in the concentrations of uterine sex steroid receptors [25,31] as well as their respective mRNAs during the estrous cycle of the sheep [27,35].…”
Section: Introductionmentioning
confidence: 99%
“…A varying portion of epithelium is denuded from the intercotyledonary endometrium by the trophoblast (Amoroso 1952). At days 0 and 28 slices of caruncular endometrium were collected using a Stadie-Riggs microtome (Miller et al 1977). The wall of the chorionic sac could be easily peeled away from caruncles at day 28.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study we examined some changes that occur in the uterus during the oestrous cycle of the ewe (Miller et al 1977). The in vitro rate of protein synthesis and RNA: DNA ratio in caruncular endometrium were maximal at or shortly after oestrus (days 0-2) and declined to low levels during the late luteal phase of the cycle (days [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The level of 'total' cytosol receptors for E2 and P were measured generally as previously described (Miller et al 1977b; except that for mice, rabbit and guinea pig tissue the phosphate in all buffers was replaced by 0·01 M Tris-HCl, pH 7 ·4. Five grams of minced sheep uterus were homogenized in 3 vol.…”
Section: Assay Of Cytosol Receptors For Oestradiol and Progesteronementioning
confidence: 99%